Advanced Wet Clean Technology at Lightly Doped Drain Layers in FinFET. (19th August 2016) - Li, Jian; Sih, Vincent; Zhan, Hui
Abstract : An advanced wet clean method to utilize piezoelectric nozzle head for fine-controlled dual-fluid sprays based on single wafer clean toolset was demonstrated on FinFET production wafers that surface particles were reduced by as much as 26% without sacrifice of gate pattern damage in sensitive lightly doped drain layers. Additionally, about 5% yield improvement was observed for using the new clean method. The fine-controlled dual-fluid sprays improved the cleaning efficiency significantly in the "physicochemical" way and reduced the potential for pattern damage caused by variations in liquid droplet size and velocity.